The Effectiveness of Giving Tumeric Tamarind in Reducing Menstrual Pain (Dismenoroe) in Young Girls at Mts Al-Muqowamah - Ai Cucu Makiyah; Nofa Anggraini (Asian Journal of Community Services, 2023)
Menstruation is a natural process for women, including young women. Data at MTs Al Miqowamah found that there were 213 young women who had menstruated, and 133 young women who experienced dysmenorrhea. This study aims to determine the effectiveness of giving turmeric acid to reduce menstrual pain (dysmenorrhoea) in young women at MTs Al-Muqowamah. This study used a pre-experimental demham design with one group pretest-posttest design. One-group pre-post test design to obtain menstrual pain data before and after the intervention. The number of samples in this study were 42 young women who met the inclusion criteria. The instrument used for data collection used a questionnaire and then the data were analyzed using the Wilcoxon test. The characteristics of menstrual pain (dysmenorrhoea) in young women before being given turmeric acid drinks included severe pain (69%) and after the intervention included moderate pain (57.1%). The results of the Wilcoxon test showed the effectiveness of giving turmeric acid to reduce menstrual pain (dysmenorrhoea) in young women at MTs Al-Muqowamah with a p value of 0.000.